Productivity and adaptability parameters of the winter bread wheat varieties developed at the FSBSI “Agricultural Research Center “Donskoy” in the southern part of the Rostov region - V. L. Chernova; S. V. Podgorny; О. V. Skripka (Зерновое хозяйство России, 2020)
The current paper has presented the three year study results (2017-2019) of the 11 winter bread wheat varieties in a competitive variety testing for productivity, environmental stability and adaptability. The purpose of the current study was to assess the ecological adaptability and stability of the winter bread wheat varieties developed at the FSBSI “Agricultural Research Center “Donskoy” in the southern part of the Rostov region. According to the data, it was found that the average productivity for 2017-2019 was 9.72 t/ha. The highest productivity was obtained in the varieties ‘Razdolye', ‘Donskaya Stepp' and ‘Univer'. In the current study the varieties ‘Razdolye' (1.26), ‘Univer' (1.09) and the standard variety ‘Ermak' (1.06) were characterized with great ecological adaptability, these varieties positively responded to the improvement of growing conditions and belonged to the varieties of intensive type. The two varieties ‘Yubiley Dona' and ‘Rubin Dona' with a regression coefficient of 1.00 were the most adaptable ones, their productivity change precisely corresponded to the changes in growing conditions. The maximum stability over the years was shown by the variety ‘Etude' (0.00). The study has proved that the highest stress resistance was demonstrated by the variety ‘Etude' (-4.14), the other varieties have shown middle values of the trait. The maximum value of genetic flexibility was identified in the varieties ‘Razdolye' (10.09), ‘Univer' (9.58) and ‘Donskaya Stepp' (9.53). The highest homeostatic indices were identified in the varieties ‘Shef' (Hom = 10.09), ‘Etude' (Hom = 9.58), ‘Donskaya Stepp' (Hom = 9.53). Taking into consideration the complex of such indicators as adptability, stability and homeostaticity, the varieties ‘Donskaya Stepp' and ‘Univer' can be charged as the most adaptive varieties among all studied.